Evaluation and selection of forage materials water stress - Cardoso Arango, Juan Andrés (Bioversity International and the International Center for Tropical Agriculture, 2022)
Having few improved forage options puts the livestock sector at risk of low productivity in the event of extreme abiotic stress events ( eg , droughts, floods). Currently, the CIAT genebank (now Alianza Bioversity -International-CIAT) and ILRI (International Livestock Research Institute) has the largest and most diverse collection of tropical forages in the world. This diversity of germplasm allows the selection of new materials with potential for adoption in different agroecological conditions in Colombia. Information related to the existing diversity in tropical forages in terms of their resistance to drought and tolerance to waterlogging can serve to improve animal production in periods of drought and extreme rainfall. Additionally, knowledge of the development of different pastures and their water demands can better recommend the most appropriate genotypes for various climates and situations, and guide grazing management and irrigation schedules.